2011
DOI: 10.1111/j.1574-6968.2011.02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of carbon from decomposing litter of two pioneer plant species into microbial communities of the detritusphere

Abstract: Initial ecosystems are characterized by a low availability of nutrients and a low soil organic matter content. Interactions of plants and microorganisms in such environments, particularly in relation to litter decomposition, are very important for further ecosystem development. In a litter decomposition study using an initial substrate from a former mining area, we applied the litter of two contrasting pioneer plant species (legume vs. pasture plants), Lotus corniculatus and Calamagrostis epigejos, which are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This assumption is based on sample timing at 89 DAI to 473 DAI. By 89 DAI, a residual effect from PLFA or enzymes from the residual litter would be minimal, especially because the litter was dried and processed before plot establishment23. Based on the results of leaf litter decomposition rates of the same experiment, we showed that forest management practices significantly influence the decomposition kinetics (BA forest has higher decomposition rate than BU forest)12.…”
Section: Discussionmentioning
confidence: 84%
“…This assumption is based on sample timing at 89 DAI to 473 DAI. By 89 DAI, a residual effect from PLFA or enzymes from the residual litter would be minimal, especially because the litter was dried and processed before plot establishment23. Based on the results of leaf litter decomposition rates of the same experiment, we showed that forest management practices significantly influence the decomposition kinetics (BA forest has higher decomposition rate than BU forest)12.…”
Section: Discussionmentioning
confidence: 84%
“…This fits with the intermediate‐disturbance hypothesis, postulating that medium disturbance events cause the highest diversification (Molino & Sabatier, 2001). However, besides the development of plant–microorganism interactions, the intermediate phase of ecosystem development is also characterized by highly efficient degradation of litter and subsequent N mineralization (Esperschütz et al , 2011) as well as an increase in fungal biomass (Bardgett & Walker, 2004), probably also of arbuscular mycorrhiza, which may contribute to a better distribution of the N in soil with ongoing succession. At this stage, the abundance and activity of nitrifiers (Nicol et al , 2005) and denitrifiers (Smith & Ogram, 2008) is still low due to the high N demand of the plants.…”
Section: Ecosystem Developmentmentioning
confidence: 99%
“…Nutrient cycles in rain forests differ with soil type, climate and topographic locations; hence, the moisture content and temperature are also unavoidable factors in the litter degradation process (Esperschutz et al 2011). …”
Section: Role Of Soil Propertiesmentioning
confidence: 99%